2019
DOI: 10.3390/cancers11040545
|View full text |Cite
|
Sign up to set email alerts
|

Identification of KIF11 as a Novel Target in Meningioma

Abstract: Kinesins play an important role in many physiological functions including intracellular vesicle transport and mitosis. The emerging role of kinesins in different cancers led us to investigate the expression and functional role of kinesins in meningioma. Therefore, we re-analyzed our previous microarray dataset of benign, atypical, and anaplastic meningiomas (n = 62) and got evidence for differential expression of five kinesins (KIFC1, KIF4A, KIF11, KIF14 and KIF20A). Further validation in an extended study sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 86 publications
(103 reference statements)
1
34
0
Order By: Relevance
“…The prognosis of patients with high level KIF-2C was worse than others [15]. It was reported that down-regulation of KIF11 decreased the proliferation of meningioma cells [16]. Accordingly, KIF11 was supposed to be the novel therapeutic target of meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients with high level KIF-2C was worse than others [15]. It was reported that down-regulation of KIF11 decreased the proliferation of meningioma cells [16]. Accordingly, KIF11 was supposed to be the novel therapeutic target of meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years new data concerning the molecular pathological background of meningiomas have been obtained. This not only facilitates the diagnosis of meningiomas but also offers the possibility to identify new prognostic and therapeutic targets [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seven members of KIF family (KIF11, KIF14, KIF15, KIF18A, KIF18B, KIF20A and KIF23) were included in the 'lightgreen' module. KIF 11 and KIF23 are the well-studies KIF family members and considered as an oncogene, inhibition of which can cause arrest at mitosis exit in hepatocellular cell carcinoma, lung cancer, pleural mesothelioma, and glioma cancer, breast cancer, meningiomas [64][65][66][67][68][69]. A phase I clinical trial on the highly selective kinesin spindle protein inhibitor, ARRY-520, has been conducted on advanced AML patients [70].…”
Section: Discussionmentioning
confidence: 99%